A RELIABILITY IMPROVEMENT OF MANAGEMENT DISTRIBUTION SYSTEM - M Fahrur Roji; Solly Aryza; Hamdani Hamdani (Jurnal Ekonomi, 2023)
The problem of load imbalance in the power distribution network system always occurs, and the cause of the imbalance is in the arrangement of single-phase loads on low-voltage network customers. As a result of the load imbalance, a current appears in the transformer neutral. Where the current flowing in the neutral of this transformer causes losses, namely losses due to the neutral current in the neutral conductor of the transformer for the distribution of electrical energy in the distribution system where voltage losses will affect the distribution of electrical energy to consumers where if there is a voltage loss in the distribution system, the electrical energy that will be distributed to consumers will be non-standard again in accordance with SPLN no. 72 of 1987, the analysis in writing this paper is to cover the extent of the voltage drop in the Palu City Rayon area, considering that the spread is an old extension. based on annual data from 2019 to 2021.